Effect Evaluation of Fault Resistance on the Operating Behavior of a Distance Relay - Le, K. H.; Vu, P. H. (Engineering, Technology & Applied Science Research, 2018)
This paper presents an application of a certain distance protection relay with a quadrilateral characteristic approach for the protection of the 110kV Duy Xuyen - Thang Binh transmission line in Vietnam using measured data from one terminal line. We propose the building process of a Matlab Simulink model for this relay that combines fault detection and classification block, apparent impedance calculation block for all types of faults and a trip logic block of three zone protection coordination. The proposed relay model is further tested using various fault scenarios on the transmission line. It is important to assess what happened, the actual conditions, the causes of mal-operation etc. Detailed explanation and results indicate that the proposed model behavior will help users to perform tests which correctly simulate real-world conditions besides that it properly interprets test results and troubleshoot distance function problems when results are not as expected.